Odpowiedzi

2010-02-14T21:46:51+01:00
√₂⁴-3√₂³+√₂²+3√₂-2

4-6√₂+2+3√₂-2

4-3√₂



proszę bardzo:)
2010-02-14T21:49:59+01:00
W(x)=x⁴-3x³+x²+3x-2
w(√2)=√2⁴-3√2³+√2²+3√2-2 = √2*√2*√2*√2-3*√2*√2*√2+√2*√2+3√2-2=
2*2-3*2*√2+2+3√2-2= 4-6√2+3√2= 4-3√2
  • Roma
  • Community Manager
2010-02-14T22:15:18+01:00
W(x) = x⁴ - 3x³ + x² + 3x - 2
W(√₂) = (√₂)⁴ - 3(√₂)³ + (√₂)² + 3√₂ - 2 = 4 - 3×2√₂ + 2 + 3√₂ - 2 = 4 - 6√₂ + 3√₂ = 4 - 3√₂

Wyjaśnienie:
(√₂)⁴ = √₂⁴ = √₂²×₂² = √₂² × √₂² = 2 × 2 = 4
(√₂)³ = √₂³ = √₂²×₂ = √₂² × √₂ = 2 × √₂ = 2√₂
(√₂)² = √₂² = 2
2 3 2